Occlusion Outcomes in Unilateral Amblyopia Types: A Longitudinal and Interventional Study in Children from the Marrakech-Safi Region - Mustapha Jaouhari; Chaimae El Harrak; Farida Bentayeb; Youssef El Merabet (British and Irish Orthoptic Journal)
Objective: To investigate if the type of unilateral amblyopia can impact the improvement of visual acuity in amblyopic eyes during a longitudinal interventional study involving standard occlusion therapy in children. Methods: A longitudinal and interventional study of 91 children, aged 3–9 years (6.12 ± 1.879) with amblyopia was undertaken. Amblyopia was unilateral and caused by either strabismus, anisometropia, or both. Amblyopia was divided into three levels of severity mild, moderate, and severe. Children underwent amblyopia treatment with standard occlusion therapy and were followed monthly, for eight visits. Results: A significant improvement in visual acuity was observed in all assessment visits across the three types of amblyopia, with a mean improvement of (0.30 ± 0.184) LogMAR. Specifically, anisometropic amblyopia with (0.28 ± 0.18) LogMAR, strabismic amblyopia (0.31 ± 0.18) LogMAR, and mixed amblyopia (0.31 ± 0.18) LogMAR. No significant differences were found between the improvement in visual acuity during the eight control visits and the types of amblyopia (r = 0.174, p = 0.182). However, a significant correlation was observed within all groups in the mean improvement in visual acuity and the severity level (r = 0.712, p = 0.034). Conclusion: Amblyopia types do not appear to significantly affect the improvement in visual acuity; however, the initial severity of amblyopia may be a key factor influencing the degree of visual recovery achieved with occlusion therapy.